Cleidocranial Dysplasia - Zabeen, B; Mohsin, F; Taher, A; Khan, MH; Azad, K; Nahar, N (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):82-84.The abstract of this article is available on the PubMed website